Asset Recovery Principles in the United Nations Convention Against Corrution 2003 (UNCAC 2003) to Support Corruption Eradication in Indonesia - Ginting, Jamin (UI Scholars Hub, 2011)
Indonesia considers the problem of corruption is one issue that cannot be handled domestically but also internationally. Based on this, international cooperation becomes essential in preventing and combating corruption, especially the attempt of corruptors to hide the corrupted assets through money laundering through an effective international transfers.There is not a small amount of public assets which had been corrupted that was stored in financial centers in developed countries that are protected both by the legal system as well as professionals hired by the corruptors. As such, the determination of International society to combat corruption is implemented through of United Nations Convention Against Corruption, 2003 (UNCAC in 2003) received by the UN General Assembly (UN SMU) on October 31, 2003 through the UN High Resolution A/58/4. This article will discuss about the position of Indonesia with regard to this matter.